The Influence of Leadership Style Toward Employee Performance in the Regional Board for Disaster Management of South Nias Regency - Duha, Timotius; Dakhi, Yohanes; Tafonao, Aluiwaauri (IJBLE Scientific Publications Community Inc., 2025)
This study aims to determine the effect of Leadership Style on Performance, at the Office of the Regional Disaster Management Agency of South Nias Regency. All employees in the research object as many as 30 people were designated as respondents. Because the type of data is primary data, therefore the data collection uses a questionnaire distribution method which is then processed with the help of IBM SPPS Statistics 23 software. The analytical tool used is simple linear regression. The test results show that the t-count value ≥ t-table value, partially the leadership style variable has a positive effect on the performance variable. Because the significanc e≤ value 0.05, it can also be stated that the leadership style variable has a significant effect on the performance variable